Áns saga bogsveigis - Eldar Heide (Edda)
ABSTRACT This article argues that the Icelandic legendary saga Áns saga bogsveigis was written as a complementary Egils saga with an alternative outcome, one in which it is not the aggressive tyrant who wins, but the farmers. To achieve this, the author uses an option that Egill’s family did not have, because it was humiliating: The hero plays the wretched fool; consequently, he is not taken seriously, and therefore he can build up power in secret until he is able to defeat the king. At the same time, Áns saga seems to be a twist on Þorsteins þáttr bǿjarmagns, which seems to be a twist on the myth of Þórr’s visit to Útgarða-Loki. In the myth, the superhumanly strong hero is unexpectedly humiliated, because his opponent controls what he sees. In Þorsteins þáttr, the hero turns the tables, because he controls what his opponent sees. In Áns saga, the herculean hero chooses to be humiliated, and this is why he unexpectedly wins.